Številčni razvoj koroških Slovencev v luči rezultatov ljudskega štetja leta 2001 - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2002)
The article presents the demographic processes within the Slovene minority in the Austrian Carinthia in the light of the temporary results of the last population census in 2001. In that census, in Southern Carinthia there were 12.586 Slovene speaking citizens or 1.376 (9.9%) fewer than a decade ago. Nowadays only the municipality of Sele has over 50% of Slovene speaking inhabitants, and 12 municipalities or 197 settlements have over 10% of Slovene population. The introductory analysis brings a survey of theory and practice of population censuses of the two Austrian republics. The relatively significant drop of the number of Slovene speakers was again affected by a number of factors, from the census methodology itself to relatively strong environment impacts and social climate, to the migration and demographic processes, and, last but not least, the principles of language and ethnic identification as well as self-identification of the Slovene origin population. Similarly to the former censuses, different factors prevailed in different surroundings in the Alpine rural municipalities most of the decrease is due to negative demographic trends and emigration, while in the urban and urbanized areas the change of the number is to a larger extent the result of the self-determination of an individual in the conditions of spatial dispersion and ethnically mixed families.
Keywords: Austria; Avstrija; narodne manjšine; zamejski Slovenci; Carinthian Slovenes; koroški Slovenci; popis prebivalstva; statistični podatki